Design of Intelligent Header for Longitudinal Axial Flow Corn Combine Harvester. Issue 1 (January 2021) - Wu, Changzhong; Ge, Fan; Shang, Guangchao; Wang, Guitao; Zhao, Mingpeng; Wu, Liang; Guo, Hengshuai
Abstract: The header is the core part of the corn harvester. This time, the main theoretical components of the header are systematically analyzed and designed to provide a basis for the manufacture of the corn harvester. The header part includes a grass divider, a stem pulling rod and a clamping conveyor chain. Stick picking is a key component of the ear picking device of a corn harvester. Therefore, it is very important to study the relationship between the movement state of corn stalks between pick sticks and the structure and movement parameters of ear picking.